Memória, trauma e fragmentação na ficção brasileira pós-64: Zero, de Ignácio de Loyola Brandão, e Em câmara lenta, de Renato Tapajós - Silveira, Tuani de Oliveira (2020)
This study aims to analyze the representation of memory, trauma, and fragmentation in the novels Zero (1975), by Ignácio de Loyola Brandão, and Em câmara lenta (1977), by Renato Tapajós, written during the Brazilian Military Dictatorship (1964-1985). The study is justi-fied because, due to the censorship imposed by the military regime, there was a ban on data and documents that stimulate the understanding of this period by researchers in the area of Human Sciences. Because of this, there is a constant need to understand the possible rela-tionships between memory, trauma, and form in novels that represented the historical period in question, characterized by authoritarianism. The novels Zero and Em câmara lenta ex-emplify, through theme and fragmented form, the traumatic impact that violence had during this period of history. Despite having distinct structures, fragmentation appears in the for-mal composition of Zero and Em câmara lenta as an attempt to represent the chaotic reality of the dictatorial period and to show the traumatic impact caused by authoritarian practices of repression and especially torture. By returning to this subject through these novels, this research enables an understanding of the society of the time from the analysis of thematic and formal strategies employed in narratives allied to the social functions of books. In add-tion, the reflections presented in this work through the comparative analysis of the novels provide a reflection on the relationship between trauma, memory, and fragmentation present in the works, proving that these books can be mechanisms of denunciation of dictatorial history. Thinking about the violence of dictatorship and how it was represented in some literary works leads to a possible understanding of the processes of constitution of the coun-try so that the practices of authoritarianism and violence should not be repeated at the pre-sent moment. To support this approach, we sought support from authors such as Sigmund Freud, Walter Benjamin, Dori Laub, Nestor Braunstein, Marcio Seligmann-Silva, Jaime Ginzburg, Regina Dalcastagnè, and Tania Pellegrini.